2012
DOI: 10.1038/tpj.2012.32
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomics of selective serotonin reuptake inhibitor treatment for major depressive disorder: genome-wide associations and functional genomics

Abstract: A genome-wide association (GWA) study of treatment outcomes (response and remission) of selective serotonin reuptake inhibitors (SSRIs) was conducted using 529 subjects with major depressive disorder (MDD). While no SNP associations reached the genome-wide level of significance, 14 SNPs of interest were identified for functional analysis. The rs11144870 SNP in riboflavin kinase (RFK) gene on chromosome 9 was associated with eight week treatment response (OR = 0.42, p = 1.04×10−6). The rs915120 SNP in the G pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
100
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(103 citation statements)
references
References 46 publications
2
100
0
Order By: Relevance
“…This study shows that glycine levels are negatively correlated to SRI treatment outcome, indicating that discrete sequence variations in genes encoding enzymes involved in glycine metabolism might contribute to the metabolomic findings. In a subsequent genome-wide association study (GWAS), the same team identified SNPs for six genes encoding enzymes in glycine biosynthesis were selectively associated to SRI response: for instance SNP rs10975641 in the glycine decarboxylase (GLDC) gene was associated with treatment outcome phenotypes (Ji et al 2012). These two studies illustrate that GWAS identify SNPs and candidate genes validating metabolic markers and pathways previously identified by metabolomics.…”
Section: Genetic Determinants Of Metabotypesmentioning
confidence: 86%
“…This study shows that glycine levels are negatively correlated to SRI treatment outcome, indicating that discrete sequence variations in genes encoding enzymes involved in glycine metabolism might contribute to the metabolomic findings. In a subsequent genome-wide association study (GWAS), the same team identified SNPs for six genes encoding enzymes in glycine biosynthesis were selectively associated to SRI response: for instance SNP rs10975641 in the glycine decarboxylase (GLDC) gene was associated with treatment outcome phenotypes (Ji et al 2012). These two studies illustrate that GWAS identify SNPs and candidate genes validating metabolic markers and pathways previously identified by metabolomics.…”
Section: Genetic Determinants Of Metabotypesmentioning
confidence: 86%
“…Similarly, DNA from patients in the STAR*D study did not reveal any positive GWA findings, and the top 25 SNPs from the STAR*D GWA analysis did not have any significant associations with treatment response [49]. In a secondary STAR*D analysis, an SNP of the riboflavin kinase gene was associated with 8-week treatment response and an SNP of the G protein-coupled receptor kinase 5 gene was associated with 8-week remission [49].…”
Section: Gene Network Studiesmentioning
confidence: 94%
“…In an 8-week trial in 499 Caucasian outpatients with nonbipolar, nonpsychotic, major depressive disorder (MDD) with mild to moderate depression treated openly with SSRIs, 398 of whom completed the protocol, genome-wide association studies did not reveal any SNPs associated with response or remission [49]. Similarly, DNA from patients in the STAR*D study did not reveal any positive GWA findings, and the top 25 SNPs from the STAR*D GWA analysis did not have any significant associations with treatment response [49].…”
Section: Gene Network Studiesmentioning
confidence: 99%
“…The Genome-Based Therapeutic Drugs for Depression (GENDEP; n = 811) study, a substudy of the Sequenced Treatment Alternatives to Relive Depression (STAR*D; n = 1,491) study, and the Munich Antidepressant Response Study (n = 339), did not find any combination of genetic markers that influenced treatment response in depression [1,44]. Genome-wide association studies did not reveal any SNPs associated with response or remission of nonbipolar, nonpsychotic, major depressive disorder treated openly with serotonin reuptake inhibitors [45], and the STAR*D study did not reveal any positive genome-wide association or top 25 SNP associations with treatment response [45]. A genome-wide association study from the Clinical Antipsychotic Trials of Intervention Effectiveness (CATIE, n = 738) did not find any combinations of genetic markers that influenced treatment response in schizophrenia [1,44].…”
Section: Gene Network Studiesmentioning
confidence: 99%